Analysis of Cultural Values in Film Denias: Humiliation in The Clouds by Ari Sihasale and Nia Zulkarnaen and its Relevance in Literature Learning in High School (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
"Analysis of Cultural Values in the Film Denias: Senandung di Atas Awan by Ari Sihasale and Nia Zulkarnaen and its Relevance in Literature Learning in High School". Film is a cultural product, which contains elements of value that can entertain the general public but also has an educational or educational dimension. Therefore, the message or message conveyed in a film (reflected in the roles or dialogue) must be able to stimulate and motivate an increase in the quality of knowledge of society in general. In other words, a film which is a work of art, can be said to be good and important when it is able to provide benefits to many people. The film "Denias, Senandung di Atas Awan", tells the story of the life of Denias, the main character, who was born as the son of a farmer from a tribe that lives in the interior of Arwanop village (the story in this film is an adaptation of the true story of a Papuan child named Janias ). This film by director John De Rantau (produced in 2006) shows various cultural aspects of the Papuan people's life journey, starting from the koteka wearing ceremony, mud bathing mourning ceremony, finger cutting and other traditional ceremonies. This research uses Roland Barthes' semiotic analysis method. This research was conducted with the aim of describing the cultural values to be conveyed through the film Denias: Senandung di Atas Awan and its relevance in literature learning